2013
DOI: 10.1016/j.bios.2012.09.066
|View full text |Cite
|
Sign up to set email alerts
|

AlGaN/GaN high electron mobility transistors for protein–peptide binding affinity study

Abstract: Antibody-immobilized AlGaN/GaN high electron mobility transistors (HEMTs) were used to detect a short peptide consisting of 20 amino acids. One-binding-site model and two-binding-site model were used for the analysis of the electrical signals, revealing the number of binding sites on an antibody and the dissociation constants between the antibody and the short peptide. In the binding-site models, the surface coverage ratio of the short peptide on the sensor surface is relevant to the electrical signals resulte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…This can be explained that above 1 ppm of hydrogen sulfide, the sensor gradually saturates, due to the limited binding sites on the interface of the Pt/GaN, which is well studied and demonstrated with binding site model previously. 19 …”
Section: Resultsmentioning
confidence: 99%
“…This can be explained that above 1 ppm of hydrogen sulfide, the sensor gradually saturates, due to the limited binding sites on the interface of the Pt/GaN, which is well studied and demonstrated with binding site model previously. 19 …”
Section: Resultsmentioning
confidence: 99%
“…The purpose of these plots is to compare a change in analyte concentration relative to a conductance change from an established baseline value. Figure 6b,c shows examples of such plots utilizing an AlGaN/GaN-based biosensor (69). These plots show three distinct regions of device operation.…”
Section: Detection Of Biomarkersmentioning
confidence: 94%
“…Several studies have reported dose response curves to assess the device sensitivity (69)(70)(71)(72). The purpose of these plots is to compare a change in analyte concentration relative to a conductance change from an established baseline value.…”
Section: Detection Of Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…FET-based biosensors have been widely used for all kinds of biomolecule detection including proteins, enzymes, DNA etc. The materials of the FET devices may include Si [2], carbon nano-tubes [3,4], or GaN [5,6]. Due to the superior sensitivity and the smaller size, the FET-based sensor plays an important role in biosensing applications nowadays.…”
Section: Introductionmentioning
confidence: 99%